Chemical Composition of Essential Oil and Hydrosol from Picea mariana Bark Residue - Nellie Francezon; Tatjana Stevanovic (BioResources, 2017)
For the first time, the essential oil of Black spruce (Picea mariana) bark residue was obtained using two types of hydrodistillations: steam distillation (SD) and water distillation (WD). Both gave similar yields and compositions as analyzed using gas chromatography and mass spectrometry. The essential oil composition is turpentine-like with the predominance of α-pinene (40.6% SD; 40.5% WD) and β-pinene (33.9% SD; 25.9% WD), followed by hydrocarbon monoterpenes β-phellandrene (4.8% SD; 3.6% WD), 3-carene (4.1% SD; 3.1% WD), and limonene (4.0% SD; 3.7% WD). Hydrosol’s composition is rich in oxygenated compounds with α-terpineol (29.3% SD; 33.5% WD), trans-pinocarveol (5.2% SD; 3.7% WD), terpinen-4-ol (5.0% SD; 5.8% WD), verbenone (4.9% SD; 5.4% WD), borneol (4.9% SD; 3.9% WD), and pinocarvone (4.6% SD; 4.3% WD). These black spruce bark essential oils differ in composition from those from needles, which are commercially available and rich in bornyl acetate.